Structures, Stability, and Safety of Diazonium Salts; Aryl Diazonium Salts and Related Compounds - Filimonov V. D. Viktor Dmitrievich (2022, 2022)
The chapter delves into the intricate structures and stability issues of diazonium salts, particularly focusing on their tendency to decompose under various conditions. It discusses the fundamental reasons behind their instability and the impact of different counterions on their stability. The text also explores the stabilization methods for diazonium salts, including the use of specific counterions and polymer matrices. Additionally, it highlights the importance of computational methods in predicting the stability and hazards associated with these compounds. The chapter concludes by emphasizing the need for caution when handling diazonium salts due to their potential hazards, and it provides insights into safer alternatives like triazenes for practical applications